Prognostic Significance of Rheological and Biochemical Findings in Patients with Intermittent Claudication. Issue 5892 (8th December 1973) - Dormandy, J. A.; Hoare, E.; Khattab, A. H.; Arrowsmith, D. E.; Dormandy, T. L.
Abstract : To assess the prognostic significance of clinical and laboratory findings in intermittent claudication a group of 62 untreated patients was followed up in detail for periods of from one to three years. There was a significant correlation between progressive deterioration of the peripheral circulatory disturbance and the initial blood viscosity, the plasma fibrinogen level, and the susceptibility of red cell lipids to autoxidation.